Effect of Suction and Injection on the Time-Varying Flow Produced by an Oscillating Porous Disk and a Newtonian Fluid at Infinity Rotating about Parallel Axes - Ersoy, H. Volkan (KAUNAS UNIV TECHNOL, 2026)
In this paper, the time-dependent flow of a Newtonian fluid generated by a porous disk performing oscillation without torsion and the fluid at infinity rotating about two different axes is considered. As the disk and the fluid at infinity are rotating non-coaxially at the beginning of the oscillation motion, the disk initiates oscillations without torsion within its own plane. The exact solutions for the velocity and shear stresses within the fluid are presented and the influences of the suction and injection are analysed. The results indicate that increasing suction leads to a reduction in the length of the space curves associated with points at which the velocity is purely axial, whereas increasing injection results in an elongation of the curves. The application of suction leads to a decrease in the boundary layer thickness whereas it increases with the implementation of injection. Furthermore, a periodic solution is presented, and the analysis confirms that the time required for the flow to become periodic is shorter for both suction and injection cases.
Keywords: Newtonian fluid; oscillating porous disk; eccen-tric rotation; exact solution; periodic flow; NON-TORSIONAL OSCILLATIONS; NONCOAXIAL ROTATIONS; UNSTEADY-FLOW; MAGNETOHYDRODYNAMIC FLOW; Mechanics